History and current state of corpus linguistics in Japan - Zhdanova , Yu.V. (Perm Federal Research Centre Journal, 2025)
The rapid development of corpus linguistics in the 1990s fundamentally changed the context of linguistic research, providing European scholars with new opportunities to work with vast amounts of language data. In Japanese linguistics, the fascinating process of creating a national language corpus has faced significant challenges for various reasons. However, in the Russian language linguistic literature, sufficient information on the state of Japanese language corpora is currently conspicuously scarce. This lacuna was partially addressed in an article by I.L. Koretskaya (2022), which attempts to outline the main Japanese language corpora available today. Nevertheless, the history of the development of Japanese corpora and its current state require more thorough description and analysis because of the urgency of solving intralinguistic issues in the Japanese language. This article traces key aspects of the history and development of Japanese language corpora, and highlights some of the difficulties that Japanese linguists have to overcome at different stages of creating a national corpus of the Japanese language.